Assesment of nutritional content of seaweed capsule from "LATO" (caulerpa racemosa). - Ferrer, Sherwin C. (College of Fisheries, University of the Philippines, 2003)
Seaweeds are rich sources of protein and iodine; this has not been fully utilized since most Filipinos do not consume them as part of their diet and is not available in all areas. Seaweeds are also the source of the most bioavailable form of iodine. Lato (caulerpa racemosa) contains natural products such as: amino acids, ether, fatty acids, fiber, lipids, minerals, nitrogenous compounds, phytohormones, pigments, polysaccharides, protein and vitamins. By concentrating essential substances from the (caulerpa racemosa) into a capsule, its nutrients can be more available to those who cannot have fresh seaweeds in their locality and to those who do not eat seaweeds. Protein and iodine extraction from lato (caulerpa racemosa) was done using 10% NaCI as extractant. An average of 6.19% recovery for extraction was obtained. Each capsule contains approximately 500-mg. extract. The capsule contains 4 times as much crude protein and 19 times as much as iodine compared to the raw material. Extraction gave an average of 25.825% recovery for the crude protein and an average of 58.57% recovery for iodine. The capsule containing 500-mg. extract will supply an equivalent of 0.6%RDA for protein and more than 100% of RDA for iodine. The obtained extract is in powdered form, grayish-green in color, water activity of 0.68 and water solubility of 4.8 mg./ml.